2013
DOI: 10.7243/2049-7962-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Volasertib (BI 6727), a novel polo-like kinase inhibitor, reverses ABCB1 and ABCG2-mediated multidrug resistance in cancer cells

Abstract: However, the most common mechanism of resistance is the active efflux of drugs by ATP-binding cassette (ABC) transporters including P-glycoprotein (ABCB1/P-gp), ABCC1/ MRP1 and ABCG2 [6]. These transporters play a key role in the energy-dependent cellular efflux of toxic agents. They are capable of recognizing and extruding a broad range of functionally and structurally unrelated compounds, thereby causing the MDR phenotype in various cancer types. An obvious strategy to restore drug sensitivity in MDR cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Since drug transporter efflux activity is associated with ATP hydrolysis, they further investigated ABC‐B1 and ABC‐G2 inhibition upon BI6727 treatment using an ATPase assay. The results from these experiments indicated that BI6727 reversed ABC‐B1‐mediated MDR by inhibition of the ATP hydrolysis, while volasertib could also act as a competitive inhibitor substrate for the ABC‐G2 transporter . In contrast, Wu et al .…”
Section: Volasertib Monotherapymentioning
confidence: 87%
See 3 more Smart Citations
“…Since drug transporter efflux activity is associated with ATP hydrolysis, they further investigated ABC‐B1 and ABC‐G2 inhibition upon BI6727 treatment using an ATPase assay. The results from these experiments indicated that BI6727 reversed ABC‐B1‐mediated MDR by inhibition of the ATP hydrolysis, while volasertib could also act as a competitive inhibitor substrate for the ABC‐G2 transporter . In contrast, Wu et al .…”
Section: Volasertib Monotherapymentioning
confidence: 87%
“…The results from these experiments indicated that BI6727 reversed ABC-B1-mediated MDR by inhibition of the ATP hydrolysis, while volasertib could also act as a competitive inhibitor substrate for the ABC-G2 transporter. 80 In contrast, Wu et al 81 found that overexpression of the ABC-B1 transporter leads to cellular resistance to volasertib treatment. For example, ABC-B1 overexpressing human epidermal cells (KB-V-1) were significantly less sensitive to the Plk1 inhibitor compared with parental cells, which was confirmed by a significant decrease in volasertib-stimulated mitotic cell cycle arrest and subsequent induction of apoptosis.…”
Section: Volasertib and Resistance To Anticancer Therapiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The recent discovery that TKIs can potently and specifically inhibit various ABC transporters has advocated the use of TKIs as chemosensitizers to circumvent MDR. In this regard, we have previously demonstrated that apatinib (Mi et al ., ; Tong et al ., ), axitinib (Wang et al ., ), crizotinib (Zhou et al ., ), vandetanib (Zheng et al ., ) and volasertib (To et al ., ) inhibit various ABC transporters and reverse MDR in leukaemia and solid tumours.…”
Section: Introductionmentioning
confidence: 99%